The Minimum Biological Energy Quantum - Müller, Volker; Hess, Verena (Frontiers in Microbiology, 2017)
Some anaerobic archaea and bacteria live on substrates that do not allow the synthesis of one mol of ATP per mol of substrate via substrate level phosphorylation. Energy conservation in these cases is only possible by a chemiosmotic mechanism that involves the generation of an electrochemical ion gradient across the cytoplasmic membrane that then drives ATP synthesis via an ATP synthase. The minimal amount of energy required for ATP synthesis is thus dependent on the magnitude of the electrochemical ion gradient, the phosphorylation potential in the cell and the ion/ATP ratio of the ATP synthase. It was always thought that the minimum biological energy quantum is defined as the amount of energy required to translocate one ion across the cytoplasmic membrane. We will discuss the thermodynamics of the reactions involved in chemiosmosis and describe the limitations for ion transport and ATP synthesis that led to the proposal that at least -20 kJ/mol are required for ATP synthesis. We will challenge this hypothesis by arguing that the enzyme energizing the membrane may translocate net less than one ion: By using a primary pump connected to an antiporter module a stoichiometry below one can be obtained, implying that the minimum biological energy quantum that sustains life is even lower than assumed to date.